Does the use of finasteride lead to sexual dysfunction?. Issue 6 (June 2018) - Nigbur, Casie; Snyder, Matthew
Abstract : EVIDENCE‐BASED ANSWER : Patients treated with finasteride are up to twice as likely to experience ejaculation disorder, decreased libido, and impotence than patients not taking finasteride (SOR: A, meta‐analysis of RCTs). The incidence of sexual dysfunction is greatest during the first year of treatment; and almost a quarter of patients will experience 1 or more sexual adverse effects during 4 years of treatment (SOR: B, RCT).